Between Athens and Paris: The life and intellectual contribution of Cornelius Castoriadis. (December 2020) - Andrews, Timothy
This paper presents a biographical outline of the life of Cornelius Castoriadis and the intersections between philosophy, politics and experience that shaped his vibrant and prolific intellectual contribution. Castoriadis grew up in Athens, at a time when Greece's internal differences came to the fore as a result of the movements of wider European history. This was a symbolic beginning that set up his migration to Paris and shaped the trajectory of this thought. In Castoriadis, we discover a fiercely independent character fixated on contributing to a more just society. In this, and in his passion for knowledge and discourse, we can detect both an Athenian citizen and a champion of the Enlightenment. In this amalgam, his location in Paris and commitment to politics are both the choices and conditions of his life and character. This paper plays on this pendulum between Athens and Paris as well as between politics and philosophy and positions Castoriadis as an Enlightenment thinker with an eye and an ear for the quotidian pulse of the social historical.